The Use of Papaya Leaves (Carica Papaya) and Calm Flower (Clitoria Ternatea) as Tea Dyed Herbs - Rahil Thahira Putri; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
This herbal tea is a variation of herbal tea made from a mixture of papaya leaves and calm flowers, which can increase the human body’s immune system. This research was conducted to determine the health benefits of herbal tea bags made from papaya leaves (Carica papaya) and calm flowers (Clitoria Ternatea). Making this herbal tea uses an expressional method. From this research, it can be concluded that this tea is widely liked because of its delicious aroma, taste, and unique texture and color. The panelists’ assessment of the taste of papaya leaves and calm flower tea was carried out using their sense of taste (tongue), then assessing the panelists’ preferences on a scale of perceived liking when tasting the tea.